Impact of Long-Term Exposure to the Tyrosine Kinase Inhibitor Imatinib on the Skeleton of Growing Rats - Tauer, Josephine T.; Hofbauer, Lorenz C.; Jung, Roland; Gerdes, Sebastian; Glauche, Ingmar; Erben, Reinhold G.; Suttorp, Meinolf (PLOS ONE, 2015)
The tyrosine kinase (TK) inhibitor imatinib provides a highly effective therapy for chronic myeloid leukemia (CML) via inhibition of the oncogenic TK BCR-ABL1. However, off-target TKs like platelet-derived growth factor receptors (PDGF-R) and colony-stimulating factor-1 receptor (c-fms), involved in bone remodeling, are also inhibited. Thus, pediatric patients with CML on imatinib exhibit altered bone metabolism, leading to linear growth failure. As TKI treatment might be necessary for a lifetime, long-term effects exerted on bone in children are of major concern. Therefore, we studied the skeletal long-term effects of continuous and intermittent imatinib exposure in a juvenile rat model. Four-weeks-old male Wistar rats were chronically exposed to imatinib via drinking water over a period of 10 weeks. Animals were exposed to a standard and high imatinib dosage continuously and to the high imatinib dose intermittently. Bone mass and strength were assessed using pQCT, micro-computed tomography (μCT), and biomechanical testing at the prepubertal, pubertal, and postpubertal age. Bone length and vertebral height as well as biochemical markers of bone turnover were analyzed. Femoral and tibial bone length were dose-dependently reduced by up to 24% (p<0.0001), femoral and tibial trabecular bone mass density (BMD) were reduced by up to 25% (p<0.01), and femoral breaking strength was lowered by up to 20% (p<0.05). Intermittent exposure mitigated these skeletal effects. Long-term exposure resulted in reduced vertebral height by 15% and lower trabecular BMD by 5%. Skeletal changes were associated with suppressed serum osteocalcin (p<0.01) and non-significantly elevated serum CTX-I and PINP levels. In conclusion, imatinib mainly impaired longitudinal growth of long bones rather than the vertebrae of growing rats. Interestingly, intermittent imatinib exposure has less skeletal side effects, which may be beneficial in pediatric patients taking imatinib.